Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpubh.2022.1047301
|View full text |Cite
|
Sign up to set email alerts
|

Climate change-related knowledge and attitudes among a sample of the general population in Egypt

Abstract: IntroductionIdentifying the public awareness and risk perception regarding climate change, are fundamental preliminary steps in determining gaps and paving the way for awareness campaigns that address climate change causes and counteraction mitigation measures. However, few studies were conducted in Egypt; thus, the researchers conducted the current cross-sectional study among a sample of the Egyptian population to identify general knowledge and perception about climate change and its effects, as well as attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…It’s expected that individuals with a more comprehensive understanding of climate change would also have a better perception of linkage between Dengue and climate change ( 5 ). This relationship is well-supported by previous researches, which consistently demonstrates that a better understanding of climate change is linked to more informed and positive attitudes about its consequences ( 4 , 48 ).…”
Section: Discussionsupporting
confidence: 83%
“…It’s expected that individuals with a more comprehensive understanding of climate change would also have a better perception of linkage between Dengue and climate change ( 5 ). This relationship is well-supported by previous researches, which consistently demonstrates that a better understanding of climate change is linked to more informed and positive attitudes about its consequences ( 4 , 48 ).…”
Section: Discussionsupporting
confidence: 83%
“…As, the total practices, attitudes and awareness scores were higher among participants who had high level of knowledge. (48) . As a result, Gerontological Nurses should apprehend the effects of climate change and promote practices that will lessen the climate change and dangerous effect on health (49) .…”
Section: Resultsmentioning
confidence: 99%
“…The maximum score was determined and the score percentage was calculated by dividing the participants’ score by the total score. The knowledge score was categorized as not knowledgeable if the percentage score was less than 70% and knowledgeable if it was 70% or more [ 8 ]. Assessment of attitudes regarding CC : Three questions were used to assess the attitudes of participants towards CC.…”
Section: Methodsmentioning
confidence: 99%
“…Also, an Indian study carried out in an urban community showed that 91.7% of participants believed that the global climate is changing [ 7 ]. Recently, in an Egyptian study by Salem et al [ 8 ], a noteworthy percentage of participants demonstrated awareness about CC (71.1%). Although CC impacts the environment globally and poses a threat to human life, research assessing CC knowledge among Egyptians is scarce.…”
Section: Introductionmentioning
confidence: 99%